The Long-Term Omalizumab Therapy in Children with Severe Persistent Uncontrolled Asthma: Evaluation of the Outcomes According to the Data of the Hospital Patient Registry - Elena A. Vishneva; Leyla S. Namazova-Baranova; Elena A. Dobrynina; Anna A. Alekseeva; Vladimir I. Smirnov; Julia G. Levina; Vera G. Kalugina; Kamilla E. Efendieva; Konstantin S. Volkov (Union of pediatricians of Russia, 2018)
Background: Patient registries help to obtain relevant information about the peculiarities of certain diseases, as well as the safety and effectiveness of different medical technologies. Moreover, it allows conducting a continuous monitoring in a studied group. Objective: to analyze the effectiveness and safety of a long-term target therapy with Omalizumab (more than 4 years) in children with severe persistent uncontrolled asthma based on the electronic clinical cases database (registry). Methods. The outcomes of the treatment were evaluated based on the data from the registry of patients with severe uncontrolled asthma. Time period: November 2007- March 2018. The main goal of the research was to identify the number of patients who achieved the disease control (20 points С-АСТ-test in children aged 6-11 years or 25 points АСТ-test in children aged 12-17 years) at least in one of the time points - in 4; 6; 12 or 48 months. Results. The results of the treatment of 26 children were analyzed (males - 73%), median age - 17 years. The posology of Omalizumab was 75 to 600 mg, median (Me) 300 mg [225; 375]. Asthma control test (ACT) before the start of the treatment was 14 points (Me 14 [12; 17,5], in 48 mo - 21 points (Me 22 [20; 24]; p=0,0017). The decrease of the amount of the daily therapy was demonstrated. The median dose of the ICS (fluticasone) was 575 mcg/day (Me 500 [437,5; 750]) before the start of the treatment, in 48 mo - 492 mcg/day (Me 500 [250; 562,5]; p=0,066). The decrease of the number of exacerbations and the use of SABA from 12 (Me 10,5 [9,75; 13,25]) to 0,8 times/month (Me [1; 0;1]) was observed after 4 years of treatment (р=0,000). No adverse events were observed. Conclusions. Long-term therapy with Omalizumab increases the disease control in children with severe persistent asthma. The registry as a continuous monitoring tool enables to conduct a complex evaluation of the effectiveness and safety of the treatment.